Engineering and Fabrication of TiO2 Photocatalyst: review - Pujiastuti, Hendrini; Kustiningsih, Indar (Chemical Engineering Department, Engineering Faculty, Universitas Sultan Ageng Tirtayasa, 2024)
The photocatalytic reactions occurring on the surface of TiO2 photocatalysts are crucial factors determining the kinetics and mechanisms of photocatalytic reactions. Photocatalyst engineering, especially of TiO2, is important due to various applications in photocatalytic processes. This review paper presents the engineering of materials and fabrication processes for TiO2 photocatalysts. Material catalyst engineering includes the development of TiO2 composites with magnetic materials, other additives, and doping. With the development of the chitosan-TiO2 coating to create the nanocomposite film, red grapes could be effectively protected against microbial infection and have their shelf life increased. F-doping on TiO₂ can increase the amount of photocatalytic oxidative species, encourage electron separation, and improve visible light absorption. To improve the effectiveness of removing the photocatalyst from the treated liquid waste once the procedure is finished, magnetic particles are added to photocatalysts. Fabrication methods for TiO2 modification to obtain specific crystal structures, including hydrothermal methods, anodization, and template-assisted techniques, will also be discussed. Another important factor is the duration of the hydrothermal treatment; nanotubes are generated after more than 12 hours. In contrast to diluted solutions, longer nanotubes will be produced during the Ti anodization process when concentrated electrolyte solutions, such as ethylene glycol and glycerol, are used.